Photojournalism : a critical analysis of training and practices in Southern Africa for training purposes - Waller, Margaret. (My University, 2000)
My thesis examines current photojoumallstic practice in Southern Africa In this examination, I introduce ways to improve existing training initiatives by incorporating critical practice into an otherwise technical education. I use 'photojoumalistic' occasions as a way of showing how a critical understanding of a situation can change the way photographs are taken and, later, read. Three specific aspects of critical practice are introduced to organise the examples into a creative and relevant learning experience. Firstly, visual literacy is introduced as a basis for learning how to read the many possible meanings of a photograph. Representation is the second aspect of critical practice. Here, the discussion focuses on specifically representations of race. Further discussions include gender and 'Culture'. Thirdly, ethics emphasises the notion of 'right action' and the (highly contested) responsibilities associated with critical practice. My contention is that photographers will be better equipped to understand and photograph the transformation processes of Southern Africa if their education incorporates a familiarity with, and articulation about, critical practice. Thus, 'photographers can be more active participants in the creation of a debate-based democratic society.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for a degree of Master of Arts in Fine Arts.
Keywords: Photojournalism.